1994
DOI: 10.1152/jappl.1994.76.6.2570
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress after human exercise: effect of N-acetylcysteine supplementation

Abstract: The association between exercise intensity and related oxidative stress was investigated in nine men who exercised for 30 min at their aerobic (AeT) and anaerobic (AnaeT) thresholds. We also tested the effect of oral N-acetylcysteine (NAC) on exercise-associated rapid blood glutathione (GSH) oxidation in subjects performing two identical maximal bicycle ergometer exercise (Max) tests. Before the second test (Max with NAC supplementation [Max(NAC)]), the men took 200 x 4 mg/day of NAC tablets for 2 days and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(100 citation statements)
references
References 0 publications
9
87
1
3
Order By: Relevance
“…Thus, several compounds that serve as cysteine precursors have been used as _alternatives to GSH, such as N-acetylcysteine (NAC), 2-oxy-4-thiazolidine-carboxylic acid (OTC), and GSH ethyl ester (91,92). Oral NAC supplementation in human subjects for two days (total dose 2.4 g) has been reported to decrease GSSG levels and blood lipid peroxidation indices provoked by an acute bout of exercise (93). Recently, Reid et al (20) showed that NAC administration improved muscle contractile functions and reduced low-frequency fatique in humans.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…Thus, several compounds that serve as cysteine precursors have been used as _alternatives to GSH, such as N-acetylcysteine (NAC), 2-oxy-4-thiazolidine-carboxylic acid (OTC), and GSH ethyl ester (91,92). Oral NAC supplementation in human subjects for two days (total dose 2.4 g) has been reported to decrease GSSG levels and blood lipid peroxidation indices provoked by an acute bout of exercise (93). Recently, Reid et al (20) showed that NAC administration improved muscle contractile functions and reduced low-frequency fatique in humans.…”
Section: Non-enzymatic Antioxidantsmentioning
confidence: 99%
“…These findings confirm the short-term activity of antioxidants in handling RONS, as well as propose a hypothesis for the stimulatory effect of acute exercise on chronic antioxidant status. However, despite the increase in antioxidant status noted in some studies, other authors have reported no increase (Sen et al, 1994;H. K. Vincent et al, 2004), which may be attributed to sampling times related to the acute session.…”
Section: Antioxidant Capacitymentioning
confidence: 67%
“…O efeito da suplementação de N-acetil-L-cisteína na oxidação de glutationa durante o exercício intenso foi testado em humanos. A su-plementação de NAC aumentou a capacidade antioxidante atenuando a taxa de oxidação de glutationa, indicando que o tratamento foi efetivo em manter o estado redox durante a atividade muscular (59) . Em adição aos experimentos em que o efeito da suplementação de N-acetil-Lcisteína no estado redox plasmático foi estudado, em experimentos utilizando músculo diafragma de rato foi mostrado que o tratamento com N-acetil-L-cisteína atenua a fadiga muscular durante contrações agudas.…”
Section: Efeito Da Suplemetação De Carboidratos E De Glutationa Na Peunclassified